The kinetics of dissolution and cluster formation of fullerene in polar and low polar solutions - N, Jargalan; D, Sangaa; T.V, Tropin; M.V, Avdeev; V.L, Aksenov (Scientific transaction of the National University of Mongolia. Physics, 2022)
Fullerene and fullerene like nanostructures play a main role in various research areas. Theamount of investigations of fullerene C60 and C70 has grown up considerably due to their several unique properties [1-2, 6]. In this report we present theoretical models for cluster growth, the modeling of small angle neutron scattering curves, and the results of structural analysis (SANS) for polar solutions of these macromolecules. Investigation of kinetics of dissolution and complex formation are studied for C60/Benzene, C60/Toluene and C60/Nmethyl-2-pyrrolidone (NMP) solutions of various concentrations by UV-Vis spectrometry. We model the kinetics of simultaneously occurring processes in the solution via a system of basic kinetic equations and obtain the corresponding parameters dependence on preparation conditions. The investigation of structural properties of fullerene solution in CS2 was performed at the YuMO instrument of the IBR-2 reactor. The results are compared tomolecular dynamics simulations, and other research works